Agroecological genomics and participatory science: optimizing crop mixtures for agricultural diversification - Chiara Santamarina; Laura Mathieu; Elena Bitocchi; Alice Pieri; Elisa Bellucci; Valerio Di Vittori; Karolina Susek; Federico Scossa; Laura Nanni; Roberto Papa (Trends in Plant Science, 2025)

Variation in radial growth sensitivity to drought among genetic groups of common yew (Taxus baccata L.) in central Italy - Enrico Tonelli; Camilla Avanzi; Elena Bitocchi; Alessandro Vitali; Andrea Piotti; Ilaria Spanu; Elena Barocci; Carlo Urbinati (Dendrochronologia, 2025)

The evolutionary history of the common bean (Phaseolus vulgaris) revealed by chloroplast and nuclear genomes analysis - Giulia Frascarelli; Teresa R. Galise; Nunzio D’Agostino; Donata Cafasso; Salvatore Cozzolino; Gaia Cortinovis; Francesca Sparvoli; Elisa Bellucci; Valerio Di Vittori; Laura Nanni; Alice Pieri; Marzia Rossato; et al. (Theoretical and Applied Genetics, 2025)
Key message The origin of common bean was investigated throughout chloroplast and nuclear WGS data considering recombination events. Our results support the Mesoamerican origin of common bean. Abstract The remarkable evolutionary history of the common bean ( Phaseolus vulgaris L. ) has led to the emergence of three wild main gene pools corresponding to three different eco-geographical areas: Mesoamerica, the Andes and northern Peru/Ecuador. Recent works proposed novel scenarios, and the northern Peru/Ecuador population has been described as a new species called P. debouckii, rekindling the debate about the origin of P. vulgaris . Here we shed light on the origin of P. vulgaris by analyzing the chloroplast and nuclear genomes of a large varietal collection representing the entire geographical distribution of wild forms including a large collection of Mesoamerican and Andean individuals. We assembled 37 chloroplast genomes de novo and used them to construct a time frame for the divergence of the genotypes under investigation, revealing that the separation of the Mesoamerican and northern Peru/Ecuador gene pools occurred ~ 0.15 Mya. Our results clearly support a Mesoamerican origin of the common bean and reject the recent P. deboukii hypothesis. These results also imply two independent migratory events from Mesoamerica to the North and South Andes, probably facilitated by birds. Our work represents a paradigmatic example of the importance of taking into account the genetic rearrangements produced by recombination when investigating phylogeny and of the analysis of wild forms when studying the evolutionary history of a crop species.

Genetic control of pod morphological traits and pod edibility in a common bean RIL population - Carmen García-Fernández; Maria Jurado; Ana Campa; Elena Bitocchi; Roberto Papa; Juan Jose Ferreira (Theoretical and Applied Genetics, 2024)
Key message QTL mapping, association analysis, and colocation study with previously reported QTL revealed three main regions controlling pod morphological traits and two loci for edible pod characteristics on the common bean chromosomes Pv01 and Pv06. Abstract Bean pod phenotype is a complex characteristic defined by the combination of different traits that determine the potential use of a genotype as a snap bean. In this study, the TUM RIL population derived from a cross between ‘TU’ (dry) and ‘Musica’ (snap) was used to investigate the genetic control of pod phenotype. The character was dissected into pod morphological traits (PMTs) and edible pod characteristics (EPC). The results revealed 35 QTL for PMTs located on seven chromosomes, suggesting a strong QTL colocation on chromosomes Pv01 and Pv06. Some QTL were colocated with previously reported QTL, leading to the mapping of 15 consensus regions associated with bean PMTs. Analysis of EPC of cooked beans revealed that two major loci with epistatic effect, located on chromosomes Pv01 and Pv06, are involved in the genetic control of this trait. An association study using a subset of the Spanish Diversity Panel (snap vs. non-snap) detected 23 genomic regions, with three regions being mapped at a position similar to those of two loci identified in the TUM population. The results demonstrated the relevant roles of Pv01 and Pv06 in the modulation of bean pod phenotype. Gene ontology enrichment analysis revealed a significant overrepresentation of genes regulating the phenylpropanoid metabolic process and auxin response in regions associated with PMTs and EPC, respectively. Both biological functions converged in the lignin biosynthetic pathway, suggesting the key role of the pathway in the genetic control of bean pod phenotype.

Genetic diversity of barley (Hordeum vulgare L.) landraces from the central highlands of Ethiopia: comparison between the Belg and Meher growing seasons using morphological traits - Tesema Tanto Hadado; Domenico Rau; Elena Bitocchi; Roberto Papa (Genetic Resources and Crop Evolution, 2009)

Genetic diversity, structure and marker-trait associations in a collection of Italian tomato (Solanum lycopersicum L.) landraces - Andrea Mazzucato; Roberto Papa; Elena Bitocchi; Pietro Mosconi; Laura Nanni; Valeria Negri; Maurizio Enea Picarella; Francesca Siligato; Gian Piero Soressi; Barbara Tiranti; Fabio Veronesi (Theoretical and Applied Genetics, 2008)